Coxsackievirus B3-Induced m6A Modification of RNA Enhances Viral Replication via Suppression of YTHDF-Mediated Stress Granule Formation - Guangze Zhao; Huifang M. Zhang; Yankuan T. Chen; Kerry Shi; Sana Aghakeshmiri; Fione Yip; Honglin Luo; Bruce McManus; Decheng Yang (Microorganisms)
N6-methyladenosine (m6A) is the most prevalent internal RNA modification. Here, we demonstrate that coxsackievirus B3 (CVB3), a common causative agent of viral myocarditis, induces m6A modification primarily at the stop codon and 3′ untranslated regions of its genome. As a positive-sense single-stranded RNA virus, CVB3 replicates exclusively in the cytoplasm through a cap-independent translation initiation mechanism. Our study shows that CVB3 modulates the expression and nucleo-cytoplasmic transport of the m6A machinery components—METTL3, ALKBH5 and YTHDFs—resulting in increased m6A modifications that enhance viral replication. Mechanistically, this enhancement is mediated through YTHDF-driven stress granule (SG) formation. We observed that YTHDF proteins co-localize with human antigen R (HuR), a protein facilitating cap-independent translation, in SGs during early infection. Later in infection, YTHDFs are cleaved, suppressing SG formation. Notably, for the first time, we identified that during early infection CVB3’s RNA-dependent RNA polymerase (3D) and double-stranded RNA (dsRNA) are stored in SGs, co-localizing with HuR. This early-stage sequestration likely protects viral components for use in late-phase replication, when SGs are disrupted due to YTHDF cleavage. In summary, our findings reveal that CVB3-induced m6A modifications enhance viral replication by regulating YTHDF-mediated SG dynamics. This study provides a potential therapeutic strategy for CVB3-induced myocarditis.